Information Distribution in Multi-Robot Systems: Generic, Utility-Aware Optimization Middleware - Barciś, Michał; Barciś, Agata; Tsiogkas, Nikolaos; Hellwagner, Hermann (Frontiers in Robotics and AI, 2021)
This work addresses the problem of what information is worth sending in a multi-robot system under generic constraints, e.g., limited throughput or energy. Our decision method is based on Monte Carlo Tree Search (MCTS). It is designed as a transparent middleware that can be integrated into existing systems to optimize communication among robots. Furthermore, we introduce techniques to reduce the decision space of this problem to further improve the performance. We evaluate our approach using a simulation study and demonstrate its feasibility in a real-world environment by realizing a proof of concept in ROS 2 on mobile robots.